Evaluasi Dampak Program Optimalisasi Lahan (OPLA) dalam Budidaya Padi di Subak Selasih Desa Puhu Kecamatan Payangan Kabupaten Gianyar - I MADE PROMETEO SEPTIA CAHYADI; I GEDE SETIAWAN ADI PUTRA; A.A.A. WULANDIRA SDJ (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
Evaluation of the impact of the Land Optimization Program (OPLA) in Rice Cultivation at the Selasih Subak of Puhu Village, Sub-District of Payangan, Gianyar Regency Population in Indonesia keeps growing with growth rate around 1,38 per year. In the last two decades, the increase rate in national food production was unable to compensate the increase rate in food needs. This reflects in increase of food product import such as rice, corn and soybean. Optimization of agricultural land is an attempt to boost the utilization of agricultural land resources into farming lands for crops, horticulture and plantation through improvements and increase of land carrying capacity. The aim of the research is to identify the program impact evaluation on the course of Special Attempt